Avoiding the greenwashing trap: between CSR communication and stakeholder engagement. (2016) - Vollero, Agostino; Palazzo, Maria; Siano, Alfonso; Elving, Wim J.L.
The paper analyses key elements of communication that may lead to accusations that a company is engaging in practices of greenwashing failing to create stakeholder engagement. According to sensemaking and sensegiving approaches, the theoretical foundations that underpin the concepts of corporate social responsibility (CSR) communication and greenwashing practices are explored and a comparison between two energy companies in the Italian and Dutch context is set up for exploratory purpose. The integration of a company's strategic CSR approach and its communication practices may help to enhance effective stakeholder engagement, prevent accusations of greenwashing and avert the negative associated consequences (e.g., scepticism among stakeholders). The research provides a theoretical contribution to CSR communication by identifying several pitfalls that can lead to the appearance of greenwashing and provides caveats for the further development of both theory and managerial practices.